Lactoferrin-derived peptide PXL01 impacts nerve regeneration after sciatic nerve reconstruction in healthy and diabetic rats - Hazer Rosberg, Derya Burcu; Mahlapuu, Margit; Perez, Raquel; Dahlin, Lars B. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAlthough advanced surgical techniques are available, satisfactory functional outcomes after peripheral nerve injuries are uncommon. Hence, immune-modulating factors such as PXL01, a lactoferrin-derived peptide that improves axonal outgrowth in injured human digital nerves, have gained attention. We previously reported a short-term immunosuppressive effect of PXL01 after the repair of transected rat sciatic nerves, but it had no effect on nerve regeneration. Here, we investigated the potential of PXL01 to improve nerve regeneration in healthy rats and in a rat model of type 2 diabetes (Goto-Kakizaki [GK] rats).MethodsA 10-mm sciatic nerve defect was created in healthy (n = 14) and diabetic GK rats (n = 14) and reconstructed using nerve autografts. Immediately after surgery, PXL01 or sodium chloride (control, placebo) (n = 7 for each treatment) was administered around the autograft. On day 8, immunohistochemical staining of the sciatic nerve and dorsal root ganglia (DRGs) was performed to analyze axonal outgrowth (neurofilament staining); inflammation (CD68 and CD206 macrophage staining in nerve); Schwann cell and sensory neuron activation (transcription factor ATF3 staining in nerve and DRGs) and apoptosis (cleaved caspase 3 staining in nerve); and neuroprotection (heat shock protein [HSP27] staining in nerve and DRGs).ResultsPXL01 had no impact on the macrophage response in the autografts but increased axonal outgrowth and HSP27 expression in the DRGs of healthy and diabetic rats, despite a lower number of activated Schwann cells in the autograft. Diabetes affected axonal outgrowth, Schwann cell and macrophage responses, and HSP27 expression. These effects were observed in the sciatic nerve as well as the DRG.DiscussionApplication of PXL01, despite having no impact on macrophages, may improve axonal outgrowth and affects Schwann cell activation in autograft-reconstructed sciatic nerves, as well as conveys neuroprotection (HSP27 expression) in the DRGs of healthy and diabetic GK rats. Diabetes influenced nerve regeneration in such autografts. Therefore, PXL01 is a promising candidate to improve nerve regeneration.